Analysis of Speech Acts of Ustadz Adi Hidayat's Lecture on Success and Happiness: A Study of Locutionary, Illocutionary, and Perlocutionary Acts - Rangkuti, Alpan Noor Habib; Supriadi, Rinaldi; Farisi, Mohamad Zaka Al; Sambo, Faisal Hamdani (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This study aims to analyze the forms of speech acts in Ustadz Adi Hidayat's lecture entitled "The Key to Success and Happiness", with a pragmatic approach through the theory of speech acts developed by J.L. Austin and John Searle. Austin's theory classifies speech acts into three types, namely locution, illocution, and perlocution, which are then further elaborated by Searle into five illocutionary categories: assertive, directive, commissive, expressive, and declarative. The method used in this study is descriptive qualitative with content analysis techniques on video transcripts of lectures. The results of the study showed that locutionary acts were used to convey literal information about Islamic values. Illocutionary acts were found in the form of assertive (affirmation), directive (advice and command), expressive (expression of emotion and belief), and interrogative (rhetorical questions). Meanwhile, perlocutionary acts successfully formed psychological and spiritual effects on listeners, such as religious awareness, increased motivation for worship, and a more transcendental orientation to life. These findings confirmed that religious lectures contained rhetorical and pragmatic power that had a significant impact on the audience. This study contributes to enriching the study of pragmatics, especially in the context of Islamic preaching communication.